The RELATIONSHIP BETWEEN MOTIVATION AND READINESS WITH STUDENTS' LEARNING ACHIEVEMENT IN DIII MIDWIFERY SEMESTER II AT AKBID PRIMA HUSADA BOGOR, 2016 - Rani Purwani (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2022)
ABSTARCT The research was conducted based on a preliminary study conducted at the Prima Husada Academy in Bogor in 2017 and found that there were many low learning outcomes for DIII midwifery students in semester II (GPA <2.75). The purpose of this study was to find out the relationship between motivation and learning readiness with learning achievement of midwifery DIII students in semester II at the Prima Husada Academy Bogor in 2017. This type of research is quantitative analytic, using a cross sectional approach. The population in this study were all second semester students of Akbid Prima Husada Bogor, namely 158 students. The samples taken were 63 students. The sampling method is simple random sampling technique and uses the Lemeshow formula. This research was conducted in May 2017. The results showed that there was a relationship between motivation and learning achievement with a P value = 0.001 (P <0.05) and there was a relationship between learning readiness and learning achievement with a P value = 0.001 (P < 0.05). Based on the results of the study it can be concluded that there is a significant relationship between motivation and learning readiness on learning achievement. It is hoped that future research will use a different research design in order to obtain different research findings.